Peran Orang Tua Terhadap Anak-Anak dalam Cerpen 'Seibei to Hyoutan' karya Shiga Naoya - Zaki Ainul Fadli; Tribuana Tunggadewi Kusumowardhani Baiquni (Universitas Diponegoro, 2022)
This study aims to determine the role of parents towards children in the short story 'Seibei to Hyotan' by Shiga Naoya published in 1913 in Japan. The research method used in this study is descriptive qualitative with data collection through literature studies. Data analysis is carried out by analyzing one of the elements of the short story structure, namely characterization and characterization, then understanding the relationship between the role of parents and children in this short story. The results showed that (1) the role of Seibei's parents towards Seibei was very important in shaping Seibei's character, (2) adults in this case the teacher from Seibei also played a role in the formation of Seibei's character, and (3) the impact of Seibei's parents' attitude towards Seibei was very large, one of which was Seibei's mistakes that recurred. <a href=